Influence of poly(ethyleneimine) functionalized multi-walled carbon nanotubes on mechanical and tribological behavior of epoxy resins. (December 2022) - Liu, Ming; Hou, Dongyang; Wu, Lixin
Abstract: Epoxy-based nanocomposites were prepared with the addition of poly(ethyleneimine) (PEI, an amine-riched polymer) functionalized multi-walled carbon nanotubes (MWCNTs), whose microstructure was characterized by TEM and FTIR spectra. Effects of PEI-functionalized MWCNTs (PEI-MWCNTs) on micromechanical properties of nanocomposites were characterized by instrumented indentation with Berkovich indenter and microscratch test with Rockwell C indenter. With the increase in the content of PEI-MWCNTs: both nanoindentation hardness and elastic modulus of nanocomposites increase; scratch normal hardness and elastic recovery rate decrease in an approximately linear way; fracture toughness obtained by scratch-based linear elastic fracture mechanics increase in an approximately linear way. Graphical Abstract: ga1